Rational cubic spline interpolation for missing solar data imputation - Karim, S.A.A. (Medwell Journals, 2018)
Missing data imputation is an important task in statistical and sciences dscipline. Solar radation data obtained from the solar tracker does not complete and some data are missing due to human error in handling the instrument or the failure of the imtnunent. Thus, missing data imputation can be used to predict and estimate the unknownvalue of the solar radation at cemin time. This study will estimate the solar radation by using rational cubic Ball spline function with three parameters. The interpolating rational Ball spline is able to give good result based on quadratic regression model. Â© 2018, Medwell Journals.